Counting and disclosure of carbon credits: a case study on company Suzano Papel e Celulose S.A - Soares, José Raryson Pedrosa; Vieira, Allan Sarmento; Ventura Júnior, Raul; Ventura, Ana Flávia Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Currently society is more present in subjects related environmental and socio-environmental issues, requiring of the government and organizations, cleaner politics, creative methods that reduce the impacts to the environment, since the business environment is seen as primarily responsible for these impacts, releasing through their activities gases that contribute to air pollution and exacerbate the greenhouse effect, such as carbon dioxide (CO2 ), raising the temperature of the planet. The principal objective of this work was to detect and calculate the carbon credits generated by the reforestation activity of the company Suzano Papel e Celulose S/A, using a quantitative method for estimating CO2 emissions avoided. In the methodological procedures used a descriptive study with a hypothetical deductive method, and a quantitative and qualitative approach to nature. Based on sustainability reporting, the data needed to obtain the results were documented. It was also possible horizontally and vertically analyze the main environmental indicators, verifying an increase in the indicator of emissions of greenhouse gases, and a reduction in harmful hazardous waste indicator. As for carbon credits, it can be affirmed that the company studied had thousands of eligible credits trading on the stock exchange in the years 2010, 2011 and 2012, but did not recognize these credits on their statements, failing to raise millions of dollars that could be invested in other social and environmental projects. Therefore, it is perceived by the results obtained, that this theme about carbon credits is of great importance and should be discussed in greater breadth and depth, both the government and regulatory bodies of accounting, should seek a parsimonious treatment that facilitates implementation of CDM and carbon credit transactions on the stock exchange.